2007
DOI: 10.1159/000104428
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA Expression of Podocyte-Associated Molecules in the Urinary Sediment of Patients with Diabetic Nephropathy

Abstract: Background: Podocyte loss plays an important role in the pathogenesis of diabetic nephropathy. We hypothesize that messenger RNA expression of podocyte-associated molecules in urinary sediment may provide important clinical information in patients with diabetic nephropathy. Method: We studied 21 patients with biopsy-proven diabetic nephropathy and 9 healthy controls. The mRNA expression of nephrin, podocin, synaptopodin, Wilms’ tumor-1 (WT-1) and α-actinin-4 in urinary sediment were measured by real-time quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 70 publications
11
76
2
1
Order By: Relevance
“…In the present study, we examined the urinary mRNA expression of podocyteassociated molecule, namely nephrin, podocin, and synaptopodin, in diabetic nephropathy patients treated with ACEI and ARB. We have previously demonstrated an increase of nephrin, podocin, and synaptopodin mRNA expression in the urinary sediment of patients with chronic kidney diseases and diabetic nephropathy (12). In the present study, we found that the urinary expression of podocyteassociated molecules correlated with baseline renal function.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, we examined the urinary mRNA expression of podocyteassociated molecule, namely nephrin, podocin, and synaptopodin, in diabetic nephropathy patients treated with ACEI and ARB. We have previously demonstrated an increase of nephrin, podocin, and synaptopodin mRNA expression in the urinary sediment of patients with chronic kidney diseases and diabetic nephropathy (12). In the present study, we found that the urinary expression of podocyteassociated molecules correlated with baseline renal function.…”
Section: Discussionsupporting
confidence: 74%
“…In the last few years, with the development of reliable RNA extraction techniques from urinary sediment and RT real-time quantitative PCR (RT-QPCR), measurement of mRNA expression in urinary sediment has become an emerging tool for the study of kidney diseases (11). Our previous crosssectional study has showed that the mRNA expression of podocyte markers, such as nephrin, podocin, and synaptopodin, in urinary sediment is increased in patients with diabetic nephropathy (12). The objective of the present study was to examine the change in gene expression of podocyte-associated molecules in the urinary sediment of patients with diabetic nephropathy after treatment with ACEI and ARB.…”
Section: Introductionmentioning
confidence: 99%
“…Podocyte count in urine sediments is a time-consuming procedure and it may be technically challenging to obtain reliable data because the reading is observer-dependent. However, recent studies have shown the feasibility of measuring mRNA of podocyte origin through quantitative reverse transcription-PCR of urine sediments (28,29). Currently, the evaluation of podocytes in the urine, although promising, cannot be considered a substitute for renal biopsy but could possibly constitute a tool for follow-up of an outpatient after biopsy-proven diagnosis.…”
Section: What Do We Know?mentioning
confidence: 99%
“…Podocyturia assessment has recently emerged as an interesting alternative biomarker. [1][2][3] Podocyturia has been identified before the onset of proteinuria in diseases such as diabetes, focal segmental glomerulosclerosis, IgA nephropathy and lupus nephritis. [4][5][6][7] Under certain conditions, apoptosis of the podocytes has been observed along with consequent detachment into the urinary space, thus leading to podocyturia and podocytopenia.…”
Section: Introductionmentioning
confidence: 99%